Optimizing Efficiency Through Sustainable Strategies: The Role of Management and Monitoring in Achieving Goals - Nuche, Asher; Sy , Omar; Carlos Rodriguez, Juan (Pandawan, 2024)
In today's rapidly evolving business landscape, efficiency is a critical aspect for organizations aiming to remain competitive and sustainable. This research explores the important roles of management and monitoring in achieving organizational goals while prioritizing sustainable practices. Effective management serves as a primary driver in formulating, implementing, and overseeing initiatives to enhance efficiency while also reducing negative impacts on the environment and society. Strong monitoring enables organizations to assess the effectiveness of sustainable initiatives, identify areas needing improvement, and track progress toward established goals. Through systematic data collection and analysis, monitoring facilitates informed decision-making, thereby enhancing the organization's ability to align actions with its sustainability objectives. The research findings indicate that effective decision-making, accurate performance measurement, good strategic planning, and strong monitoring mechanisms significantly influence organizational productivity and the achievement of company goals. By reinforcing management practices and monitoring mechanisms, organizations can optimize operational efficiency and achieve strategic goals sustainably.